AB0226 Role of MRI in Diagnosing Patients of Early Arthritis with Suspicion of RA/Undifferentiated Arthritis Presenting Serologically and Clinically as Diagnostic Dilemma in Indian Population. (10th June 2014) - Pandey, B.
Abstract : Background: 47% of patients of RA have normal serology and no evidence of clinical synovitis posing a various diagnostic dilemma to the clinician. EULAR guides treat to target strategy in suspected patients of arthritis. Window of opportunity exists in initiation of early and aggressive treatment of arthritis to prevent further damage. Objectives: 1.To be able to overcome the diagnostic dilemma of a disease affecting the joints being early arthritis in a set up of clinical and serological findings not being able to be helpful in making the diagnosis of ongoing inflammatory process. 2.The relationship of arthritic disease with carotid intimal thickness as a risk factor for cardiovascular disease in these patients. Methods: A total of 33 patients 21 females and 12 males were studied. 25 patients were in age group of 45-78 years, 6 patients were in age group of 28-38 years and one patient of 15 years age, who were strongly suspected of early RA or undifferentiated arthritis were clinically and serologically worked up, when the diagnostic dilemma still persisted contrast enhanced MRI of the clinically more affected hand was done and scoring of synovitis, bone marrow edema, bone erosions were done according to RAMRIS. The finding of tenosynovitis, enthesitis, periostitis were also recorded. In such a equivocal scenario only 1 patient showed thrombocytosis, 4 patients were RF positive, 4 patients were Anti CCP positive, 18 patients showed raised ESR, 7 patients showed raised CRP, 7 patients showed raised ANA, 4 patients were hypothyroid and one patient had Anti Rho/La positive. Bilateral carotid intimal thickness were taken at a distance of approximately 2cm proximal to the carotid bulb. Results: Out of the examined patients 28 showed synovitis, 7 showed bone marrow edema, 12 patients showed erosions and 9 patients showed tenosynovitis, just 2 patients showed normal MRI findings.12 patients showed raised carotid intimal thickness. Conclusions: MRI in the setting of serological and clinical limitation of diagnosing early or undifferentiated arthritis is of great help in establishing an undubious diagnosis of ongoing inflammatory changes in the synovium associated with or without erosions, bone marrow edema or just the presence of mere tenosynovitis and aided the clinician to stick to the goal of treat to target strategy.The study was helpful in guiding the clinician so as to start an aggressive or nonaggressive treatment. Carotid intimal thickness did not relate well as a risk of cardiovascular disease in such patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5078